Penerapan Smart WiFi Plug dalam Meningkatkan Efisiensi Energi Penerangan Jalan Umum - Fikri Fahmi, Muhammad; S.P Silitonga, Gerson; Rama Insiyanda, Dita (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This community service activity aims to improve energy efficiency in public street lighting systems through the application of Smart WiFi Plug technology based on the Internet of Things (IoT). The innovation was implemented as a concrete effort to support energy-saving initiatives and the development of smart city infrastructure. The activity was carried out in the surrounding area of the Indonesian Land Transport Polytechnic (STTD) campus in Bekasi, involving local residents and public lighting managers. The implementation stages included a preliminary survey to identify existing conditions, technical training on device usage, installation and testing of Smart WiFi Plug, and evaluation of energy efficiency and operational costs. The results indicated an average reduction of 34–36% in electricity consumption compared to pre-installation levels, along with increased public awareness of technology-based energy management. In addition to its economic impact through operational cost savings, this activity contributed to reducing carbon emissions and strengthening community capacity in adopting environmentally friendly digital technologies. This program is expected to serve as a sustainable model for community empowerment that promotes public energy efficiency and supports the realization of smarter, more efficient, and sustainable environments.